2007
DOI: 10.1073/pnas.0703739104
|View full text |Cite
|
Sign up to set email alerts
|

Maternal nutrient supplementation counteracts bisphenol A-induced DNA hypomethylation in early development

Abstract: The hypothesis of fetal origins of adult disease posits that early developmental exposures involve epigenetic modifications, such as DNA methylation, that influence adult disease susceptibility. In utero or neonatal exposure to bisphenol A (BPA), a high-production-volume chemical used in the manufacture of polycarbonate plastic, is associated with higher body weight, increased breast and prostate cancer, and altered reproductive function. This study shows that maternal exposure to this endocrine-active compoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
890
2
11

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 1,226 publications
(940 citation statements)
references
References 48 publications
26
890
2
11
Order By: Relevance
“…Methylation differences reported in this study are small as compared to those reported at the A vy locus in BPA-exposed animals 40 and in human liver cancer pathology, 41 but are similar to effect sizes reported at other epigenetic loci in A vy mice exposed to BPA. 24,42 Further, several comparisons yielded p-values between 0.05 and 0.1, indicating that several additional data points may have reached our chosen threshold for statistical significant (P<0.05) given a larger sample size and therefore greater power to detect small effect sizes.…”
Section: Assay Forward Primersupporting
confidence: 80%
“…Methylation differences reported in this study are small as compared to those reported at the A vy locus in BPA-exposed animals 40 and in human liver cancer pathology, 41 but are similar to effect sizes reported at other epigenetic loci in A vy mice exposed to BPA. 24,42 Further, several comparisons yielded p-values between 0.05 and 0.1, indicating that several additional data points may have reached our chosen threshold for statistical significant (P<0.05) given a larger sample size and therefore greater power to detect small effect sizes.…”
Section: Assay Forward Primersupporting
confidence: 80%
“…Such exposure also decreases methylation of the cancer-causing oncogene c-fos (121) and the estrogen-responsive gene lactoferrin in mice (122). In animals, in utero or neonatal exposure to bisphenol A is associated with higher body mass, altered reproductive function, increasing cancer risk, and specific DNA methylation changes (123)(124)(125).…”
Section: Endocrine Disruptorsmentioning
confidence: 99%
“…Indeed, folate (and diet in general) may be just the tip of an iceberg of epigenetic modulators. Exposure to environmental chemicals can affect DNA methylation in pregnant mice (20), and in vitro fertilization was associated with incomplete epigenetic reprogramming at some loci in children (21), raising the fear that each of these events may lead to constitutional defects such as that reported by Wong et al in this issue of the journal.…”
mentioning
confidence: 94%